Efficiency of Multislice Computed Tomography in Diagnosis of Coronary Artery Disease compared to Cardiac Catheterization - Elhussein, Nagwan; Ahmed, Rania Mohammed; AL-Thobity, Rawan; Al-Qurashi, Hadeel; AL-Sulimani, Shahad; AL-Turgi, Shmookh; AL-Zaidi, Wasyf; Al-Sufyani, Basma; Kazim, Mameedullah (International Journal of Innovative Research in Medical Science, 2019)
Coronary artery disease (CAD) is a leading cause of mortality and morbidity in developed countries, although percutaneous coronary intervention and coronary artery bypass grafting have developed recently, also multislice computed tomography has been accepted tool for diagnosing of (CAD). Objective: To assess the efficiency of multislice computed tomography in diagnosing coronary heart disease compared with cardiac catheterization. Method: This retrospective study was conducted at Alhada Military hospital in Taif City, Saudi Arabia, in radiology and cardiac catheterization departments during period from January to April 2018. The study was done by collecting of 51 patients reports of computed tomography and coronary artery catheterization most of them complain of chest pain. Data was analyzed using statistical package for social sciences program (SPSS) version 21.00. And achieved in tables and graphs in percentages according to the age, gender, patient history, symptoms, CT finding and catheterization finding, from the check list. Results: The most common affected age group was (61-80)y, male were (52.9%), the most complain was chest pain. CT scan positive findings were found to be in (72.5%) of the patients, while the cardiac catheterization diagnosed (CAD) in (68.6%) of the patients, there are statistical significance difference between the CT and cardiac catheterization finding (P=0.00), but there were no statistical significance difference between cardiac catheterization finding with age and gender among study sample. Conclusion: CT scan can accurately diagnose the coronary artery disease, which is an ideal non-invasive technique compared with cardiac catheterization.